Humble Leadership and Team Innovation: The Mediating Role of Team Reflexivity and the Moderating Role of Expertise Diversity in Teams - Lei, Xinghui; Liu, Wei; Su, Taoyong; Shan, Zhiwen (Frontiers in Psychology, 2022)
The current study proposes a moderated mediation model to explain the relationship between humble leadership and team innovation. Integrating social information processing theory with the existing literature onhumble leadership, we hypothesize that when a humble individual leads a team, the members of the team are more likely to reconsider their strategies, review past events with self-awareness, share diverse information and adapt to new ideas, which in turn promotes innovative team activities. Moreover, consistent with the research that emphasizes the inclusion of team culture in exploring leader-innovation relationships, we investigate the moderating role of expertise diversity in the above positive indirect relationship. We test our model by using both archival and survey data that were collected from 135 teams within 18 medium-to -large firms in the internet technology industry of China. The findings largely support our theoretical assertions, suggesting that humble leadership has important implications for team processes and innovation.